A Highly Crystallized Hexagonal BCN Photocatalyst with Superior Anticorrosion Properties. Issue 15 (1st May 2022) - Guo, Fangsong; Li, Shanrong; Yang, Can; Zhang, Jinshui; Hou, Yidong; Wang, Xinchen
Abstract: A major challenge in the nitride‐based materials for photocatalytic oxidation reaction is their low stability under oxidizing and acidic environment. To solve these problems, highly crystallized hexagonal boron carbon nitride (BCN) with more homogeneous mixing of B, C, and N atoms is achieved by pyrolysis of precursor materials in the presence of NaOH as a crystallization promoter. The high crystallinity and chemical homogeneity features of the fabricated BCN reduce the structural defects and accelerate the interfacial charge transfer and separation, thus inhibiting the self‐oxidation and endowing it with a superior oxidation resistance. With these prominent advantages, the highly crystallized BCN exhibits markedly enhanced photocatalytic activity and long‐term anticorrosion stability under oxygen and self‐generated acidic condition, far beyond polycrystalline BCN. This work offers new insights into the catalyst design of crystalline BCN and demonstrates its great promise for solar energy applications. Abstract : Highly crystallized hexagonal boron carbon nitride with chemical homogeneity synthesized by adding crystallization promoter endows it with super resistance to self‐oxidation and excellent activity for photocatalytic oxidation.